Missing the meaning and provoking resistance; a case of myalgic encephalomyelitis. - Butler, C; Rollnick, S (1996)
BACKGROUND: The interaction between a clinician and a patient who put his problems down to myalgic encephalomyelitis is described. Despite attempting a patient-centred approach, the doctor acted on his own understanding of the meaning of this diagnosis without gaining proper insight into what it meant for the patient. This failure not only led to damaged rapport, it may have contributed to delayed recovery. OBJECTIVES: The unsatisfactory nature of this encounter led the clinician to consider more effective consulting techniques. METHODS AND RESULTS: A hypothetical interaction is constructed in which the clinician uses reflective listening statements to understand the patient's true meaning of this self-diagnosis. CONCLUSIONS: Despite well intentioned attempts to be patient-centered through widening the consultation beyond the biomedical to include personal and contextual factors, clinicians may still end up imposing their own medical meaning on patient's words. Damaged rapport is a signal that another track could be more fruitful and reflective listening is one strategy which enables clinicians to check that they fully understand the patient's meaning. Provoking resistance by following strategies which are not appropriate for the patient might then be avoided.